Analysis of seasonal differences in emergency department attendance in Shiga Prefecture, Japan between 2007 and 2010. Issue 2 (14th July 2015) - Otsuki, Hideki; Murakami, Yoshitaka; Fujino, Kazunori; Matsumura, Kazuhiro; Eguchi, Yutaka
Abstract : Aim: Emergency department overcrowding is problematic. Some emergency departments have established a triage system to prevent overcrowding; however, effective management of a triage system requires knowledge of factors that influence emergency department attendance. Therefore, we investigated the effect of ambient temperature on emergency department attendance, as well as the types of patients that may have been affected. Methods: Data on emergency department attendance at Shiga University of Medical Science Hospital (Otsu, Japan) were retrospectively collected from 1 April, 2007 to 31 March, 2010. Attendance was classified into eight categories based on a combination of symptoms (trauma or non‐trauma), transport (by ambulance or walk‐in), and severity (serious or non‐serious). Results: A total of 7, 755 patients (4, 120 [53.1%] men and 3, 635 [46.9%] women) attended the emergency department during the study period. Statistically significant seasonal differences were observed in emergency department attendance in walk‐in and non‐serious groups of both trauma and non‐trauma patients ( P < 0.01), with the smallest differences occurring during winter. In a linear regression model, the mean ambient temperature had a positive correlation with emergency department attendance only in the walk‐in and non‐serious group of non‐trauma patients during the summer (y = 0.092 × [mean ambient temperature] − 0.565). Conclusion: In the walk‐in and non‐serious group of non‐trauma patients, emergency department attendance significantly increased with the increase in mean ambient temperature during summer. In emergency department triage systems, it may be more effective to evaluate non‐trauma and walk‐in patients during summer, especially on hot days.